2014
DOI: 10.1002/bmc.3212
|View full text |Cite
|
Sign up to set email alerts
|

Validation of LC‐MS/MS method applied to evaluation of free tissue concentrations of vildagliptin in diabetic rats by microdialysis

Abstract: A novel LC-MS/MS method was developed for the quantification of vildagliptin in an aqueous matrix. The method was successfully validated, meeting all the requisites of US Food and Drug Administration guide for a bioanalytical method. The developed method presented a limit of quantification of 10 ng/mL and the range of concentration achieved was 10-1875 ng/mL. The injection volume necessary was only 10 μL, and retention time was 4.60 min. The mobile phase employed was methanol-ammonium acetate 5 mm (95:5). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Pharmacokinetic studies were performed in normal, healthy, male Wistar rats. [13] The rats were divided into three groups (n = 6), and were administered CR, RN and RNM suspensions orally at a dose of 50 mg As2S2/kg body weight using a gavage needle. After administration, about 0.5 ml blood sample was collected from the ocular vein into a haeparinized tube in accordance with a programmed schedule at 0.5, 1, 2, 3, 4, 6, 8, 12, 24, 36 and 48 h. The collected samples were dispelled using microwave and then assessed by HGAAS method.…”
Section: In-vivo Bioavailabilitymentioning
confidence: 99%
“…Pharmacokinetic studies were performed in normal, healthy, male Wistar rats. [13] The rats were divided into three groups (n = 6), and were administered CR, RN and RNM suspensions orally at a dose of 50 mg As2S2/kg body weight using a gavage needle. After administration, about 0.5 ml blood sample was collected from the ocular vein into a haeparinized tube in accordance with a programmed schedule at 0.5, 1, 2, 3, 4, 6, 8, 12, 24, 36 and 48 h. The collected samples were dispelled using microwave and then assessed by HGAAS method.…”
Section: In-vivo Bioavailabilitymentioning
confidence: 99%
“…Linagliptin was reported to be quantitatively analyzed using HPLC [32] and LC-MS/MS [33,34] techniques. Metformin and alogliptin in combined formulation were estimated by HPLC [35,36], whereas vildagliptin was analyzed by different chromatographic methods using LC-MS/MS [37] and reverse phase-HPLC [38,39]. In addition to that, HPLC methods for the simultaneous determination of more than one DPP-4 inhibitors in dosage forms have also been reported in the literature [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The technology is time-resolved and space-resolved, providing free small-molecule compounds. Microdialysis for use in PK and PD research has been applied and developed, and a large amount of literature has been reported [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%